Suggestioni postdrammatiche di un teatro di confine (Itinera, 2013)
In detention centers, as in marginal contexts in general, theater crosses over into the social sphere. As with many efforts of this type, it may follow different paths than official theater, focusing on aspects related to the value of human beings. An out of bounds theater, part of the so-called “theater of diversity”, is based on the idea of community theater and designed to enhance and develop individual inclinations and abilities in a group context. The end product of this approach to theater is a dynamic performance, an object which, according to the categories suggested by Peirce, displays signs that are interposed between the object and its interpreter, forming a ground that is translated into social significance. This is a kind of theater that, because of the spectator’s reaction, falls into a postdramatic context, where the acting materializes the dramatic subject and his world, affirming his identity through a real body in a real space.